Rhodium Nanoparticles Loaded on Carbon‐Wrapped Fe3O4 Sphere: an Efficient, Stable and Magnetically Recoverable Catalyst for the Catalytic Transfer Hydrogenation of Nitroarenes in Water. Issue 23 (16th August 2017) - Zhou, Junjie; Chen, Zhangpei; Hu, Zenan; Li, Kang; Ai, Yongjian; Li, Shuang; Qi, Li; Tang, Zhike; Liu, Lei; Sun, Hong‐bin
Abstract: The carbon wrapped magnetic nanosphere Fe3 O4 @C (∼300 nm) was prepared under simple hydrothermal conditions, and it served as the carrier of Rh nanoparticles (2‐3 nm), which acted as the highly efficient catalyst for reduction of nitro compounds, and reutilization of catalyst is convenient to achieve because the catalyst particles are magnetic. A scope of nitroarene derivatives were reduced to corresponding anilines in water, and the reactions completed in 10 min with nearly quantitative conversions and 100% selectivity. In addition, the abundant oxygen‐containing functionality on the carbon shell which can strongly binds the Rh‐NPs to offer extraordinary stability is investigated by using various techniques, including transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS), X‐Ray Diffraction (XRD), and Fourier transform infrared spectrometer (FT‐IR). Abstract : The core‐shell structure nanocomposite Fe3 O4 @C‐Rh was prepared and used as the magnetically recoverable catalyst for the catalytic transfer hydrogenation of nitroarenes to arylamines. The reaction was carried out in water using hydrazine hydrate as hydrogen source. During the reaction, the Rh NPs were immobilized on the surface of carbon shell due to the existence of oxygen containing functional groups, and the catalytic system showed high conversion and selectivity even other reducible groups remained.